Posture‐Related Differences in Cardiovascular Function Between Young Men and Women: Study of Noninvasive Hemodynamics in Rural Malawi - Manoj Kumar Choudhary; Roosa‐Maria Penninkangas; Arttu Eräranta; Onni Niemelä; Charles Mangani; Kenneth Maleta; Per Ashorn; Ulla Ashorn; Ilkka Pörsti (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Cardiovascular risk is higher in men than in women, but little information exists about sex‐related differences in cardiovascular function from low‐income countries. We compared hemodynamics between sexes in rural Malawi in a cohort followed up since their birth. Methods and Results Supine, seated, and standing hemodynamics were recorded from 251 women and 168 men (mean age, 21 years; body mass index, 21 kg/m2) using oscillometric brachial waveform analyses (Mobil‐O‐Graph). The results were adjusted for estimated glomerular filtration rate, and plasma potassium, lipids, and glucose. Men had higher brachial and aortic systolic blood pressure and stroke index regardless of posture (P<0.001), and higher upright but similar supine diastolic blood pressure than women. Regardless of posture, heart rate was lower in men (P<0.001), whereas cardiac index did not differ between sexes. Women presented with lower supine and standing systemic vascular resistance index (P<0.001), whereas supine‐to‐standing increase in vascular resistance (P=0.012) and decrease in cardiac index (P=0.010) were higher in women. Supine left cardiac work index was similar in both sexes, whereas standing and seated left cardiac work index was higher in men than in women (P<0.001). Conclusions In young Malawian adults, men had higher systolic blood pressure, systemic vascular resistance, and upright cardiac workload, whereas women presented with higher posture‐related changes in systemic vascular resistance and cardiac output. These findings show systematic sex‐related differences in cardiovascular function in a cohort from a low‐income country with high exposure to prenatal and postnatal malnutrition and infectious diseases.